Utilization of Social Media as a Quarter Life Crisis Education Media - Rahmayanti, Sheilla; Pramudya, Dandy Arie; Hayuningrat, Fathimah Az-Zahra; Esrarf, Lubna Salsabila; Naia, Nisrina Alifah; Ariyanto, Khansa Salsabila Putri; Nazila, Yasmin; Almutairi, Reem Iafi (Tarqabin Nusantara Group, 2023)
Introduction : Quarter life crisis is an individual's response to moving towards the reality of life in which there is instability, continuous change, various choices and the emergence of panic due to feeling helpless. Life changes like this are accompanied by the emergence of various kinds of emotional reactions such as anxiety, panic, stress, and confusion about goals, as well as doubts about one's own abilities and fear of failure. Methods: in utilizing social media, using qualitative methods, which include collecting data by interviews and delivering material. Purpose: to take an approach involving visual narratives, interviews, and practical solutions in providing a comprehensive view of the quarter life crisis and providing positive value in using social media and having a good impact on oneself. Results: The author's video has its own interest among Instagram users, as evidenced by the author's video views reaching 3,753 and video likes reaching 89 likes. This shows that Instagram users gain knowledge about the quarter life crisis. Conclusion: Currently there are still students who experience changes in emotional reactions such as anxiety, panic, stress, and confusion and doubt about their own abilities. Video about the quarter life crisis by conducting interviews with students to get various perspectives on the quarter life crisis and strategies for dealing with it. The video content will be disseminated via social media such as Instagram.